Consumer Purchase Intention toward Contemporary Coffee Products: the Effect of Price, Promotion, and Service Quality (Study at Kopi Kenangan Mantan) - Fachru Sabrina Aulia Br. Ginting; Elysia Elysia; Lenta Friska Purba; Yan Raja David Hamonangan Damanik (SEAN Institute, 2026)
This study examines consumer purchase intention toward contemporary coffee products through the influence of price, promotion, and service quality, with a specific focus on the Kopi Kenangan Mantan menu. A quantitative approach with an explanatory research design was applied. The research was conducted at Kopi Kenangan Medan, involving 100 respondents who had purchased products from Kopi Kenangan. Data were collected through structured questionnaires and analyzed using multiple linear regression. The results show that price has a positive and significant effect on consumer purchase intention, indicating that consumers consider price suitability, affordability, and perceived value before making a purchase. Promotion also has a positive and significant effect, suggesting that digital promotions, discounts, vouchers, and attractive marketing campaigns can increase consumer interest in buying the product. In addition, service quality positively and significantly affects purchase intention, showing that fast service, employee friendliness, order accuracy, and transaction convenience contribute to a positive consumer experience. Simultaneously, price, promotion, and service quality significantly influence consumer purchase intention. These findings indicate that consumer interest in purchasing the Kopi Kenangan Mantan menu is shaped by the combination of perceived price fairness, effective promotional strategies, and satisfactory service quality.